Child malnutrition, consumption growth, maternal care and price shocks: new evidence from Northern Ghana. Issue 1 (1st January 2020) - de Groot, Richard; Handa, Sudhanshu; Ragno, Luigi Peter; Spadafora, Tayllor; ,
ABSTRACT: Childhood malnutrition remains a significant global health concern. In order to implement effective policies to address the issue, it is crucial to first understand the mechanisms underlying malnutrition. This paper uses a unique dataset from Northern Ghana to explain the underlying causes of childhood malnutrition. It adopts an empirical framework to model inputs in the production of health and nutrition, as a function of child, household and community characteristics. The findings suggest that maternal agency and health contribute to improved health status. Household resources – in the form of consumption – are positively associated with food intake and nutritional outcomes. Simulations show that income growth, improving maternal care and avoiding sudden price shocks have a positive – but rather limited effect – on the reduction of malnutrition in this context. Effects are greater in children under two. Hence, policies that address underlying determinants simultaneously, and target the youngest population of children, could have the largest effect on reducing malnutrition in this population.